The Wooden Gong - Akpan, N.U (Longman Group Ltd, 1965)
Chief Inam had been embarrassingly caught between the contradictory forces of conservative tradition and incipient Christian progress, both of which he equally liked, cherished,and was anxious to foster and maintain$1! =s
Keywords: Fiction